Market brand equity: lost in terminology and techniques?. Issue 6 (19th September 2016) - Schultz, Don
Abstract : Purpose: The purpose of this paper is to review, update and suggest new approaches to estimate/determine market brand equity (MBE) impact based on additional brand investments in existing brands. The approach can be used by senior managers, replacing traditional return-on-investment (ROI) historical approaches. The paper focuses on the brand owner's values/returns rather than those of the customer/consumer. Design/methodology/approach: A conceptual approach using a theoretical methodology based on a literature review and informed analysis of how a new type of MBE estimation/calculation methodology might be developed. Findings: This paper proposes a radically different, forward-looking calculation/estimation of MBE determination based on estimations of additional cash flows which might return to the firm as a result of additional investments made in the brand. The approach moves away from traditional cost/managerial accounting approaches to a more actuarial-based estimation of future income flows should additional investments be made in the brand. A Markov chain or other probability-based methodology of estimating future returns is suggested. Originality/value: Presently, most brand investment models are based on historical backward-looking estimations/calculations of snapshots of point-in-time ROI models. These, the author argues, are outdated and irrelevant for forward-looking managers and firms. This recommended approach provides senior management with estimates of the value that might be created in the future.